Increased blood-brain barrier permeability correlate with microglial activation at hippocampal CA1 region in acute and chronic bilateral common carotid artery ligation in rats - Dian Prasetyo Wibisono; Nur Arfian; Handoyo Pramusinto; Fauziyatul Munawaroh; Yeshua Putra Krisnugraha; Daniel Agriva Tamba; Dwi Cahyani Ratna Sari (Universitas Gadjah Mada, 2022)
Inflammatory processes might play a key role in the pathogenesis of post-stroke epilepsy. The activation of microglia and release of vascular cell adhesion molecule-1 (VCAM1) might induce blood-brain barrier (BBB) disintegration. However, the influence of such pathomechanisms in the generation of post-stroke epilepsy is still not clear. We investigated whether cerebral ischemia exerts effects on inflammation in the hippocampus by measuring the hippocampal injury score, expression of a microglial marker, and expression of VCAM1 in rats. A total of 24 Sprague Dawley rats were randomized into four groups with 6 rats in eachgroup i.e. sham operation (SO) as control, carotid ligation 1 (GCL1) as an acute model, carotid ligation 3 (GCL3) as a subacute model, and carotid ligation 7 (GCL7) as a chronic model. Immunostaining for microglia marker (CD68) was measured in rat brain tissue sections. The VCAM1 expression was evaluated by reverse transcription-polymerase chain reaction (RT-PCR). Cerebral ischemia increased the amount of microglial immunostaining and expression of VCAM1. The hippocampal injury score and microglial immunopositivity were significantly correlated with the duration of brain ischemia. We conclude that cerebral ischemia is correlated with neuroinflammatory reaction and disturbance of BBB permeability, and the correlation of those molecular impairments with the generation of post-stroke epilepsy remains to be elucidated.